2012
DOI: 10.1038/emboj.2012.324
|View full text |Cite
|
Sign up to set email alerts
|

A gene loop containing the floral repressor FLC is disrupted in the early phase of vernalization

Abstract: Gene activation in eukaryotes frequently involves interactions between chromosomal regions. We have investigated whether higher-order chromatin structures are involved in the regulation of the Arabidopsis floral repressor gene FLC, a target of several chromatin regulatory pathways. Here, we identify a gene loop involving the physical interaction of the 5 0 and 3 0 flanking regions of the FLC locus using chromosome conformation capture. The FLC loop is unaffected by mutations disrupting conserved chromatin regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 60 publications
(131 reference statements)
5
151
0
1
Order By: Relevance
“…As reported previously, loop formation was reduced by vernalization in the wild type (Crevillén et al, 2013). Interestingly, we observed that the FLC loop was more stable after vernalization in both RNAi lines ( Figure 8D), and these observations were in agreement with the expression data and the phenotype observed.…”
Section: Baf60 Is Necessary For Efficient Disruption Of the Flc Loop supporting
confidence: 81%
See 4 more Smart Citations
“…As reported previously, loop formation was reduced by vernalization in the wild type (Crevillén et al, 2013). Interestingly, we observed that the FLC loop was more stable after vernalization in both RNAi lines ( Figure 8D), and these observations were in agreement with the expression data and the phenotype observed.…”
Section: Baf60 Is Necessary For Efficient Disruption Of the Flc Loop supporting
confidence: 81%
“…Surprisingly, the FLC loop was not disturbed by mutations that affect several chromatin regulatory pathways and lead to different expression levels (Crevillén et al, 2013), indicating that expression of FLC can be modulated independently of the spatial organization at this locus. However, the formation of this loop may mediate the vernalization pathway for FLC regulation, since its formation was disrupted during vernalization, concomitant with the downregulation of FLC.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations